Rebuilding Borders: Artsakh's Protestant Communities in Armenia - Gabrielyan , Lilit (History and Culture, 2025)
This article examines the impact of the forced displacement of Protestant Artsakh Armenians in 2023 on religious communities, focusing on the construction, destruction, and interactions of imagined religious boundaries within Armenian Protestant communities. Before the displacement of Artsakh, Protestant communities had clearly defined religious, social and economic boundaries in Nagorno-Karabakh, with long-established religious structures and communal social ties. The study shows how displacement leads to the destruction of these borders and the formation of new, imaginary borders. The article also discusses the socio-cultural and psychological challenges that the Artsakh Armenians faced when crossing the Armenian border, the role of faith, the increased demand for miracles in times of danger, as well as the problems of reconfiguring cultural, linguistic and domestic borders in new social landscapes. The article was based on the magazines of the Armenian Evangelical Church and the whole Church of Christians of the Gospel faith (Pentecostals), publications on official websites, interviews conducted by me with pastors of these churches, church members and believers displaced from Artsakh.